DIFFERENTIATED INSTRUCTION IN ONLINE LEARNING: ITS BENEFITS AND CHALLENGES IN EFL CONTEXTS - Ayuningtyas, Luh Putu Swasti; Suwastini, Ni Komang Arie; Dantes, Gede Rasben (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
As one consequence of the massive ICT development, online learning has played a great role in current educational practices. However, even though the learning process is conducted online, students’ diversity needs to be considered to assist them in unlocking their fullest potential in learning. Differentiated instruction can facilitate students’ diverse cognitive abilities, interests, readiness, and learning profile. This research aimed to elaborate on the benefits and challenges of implementing differentiated instruction in online learning. Through systematic library research, the study revealed that differentiated instruction in online setting is argued to benefit students’ reading, speaking, listening, and writing skills. The challenges identified in the implementation of differentiated instructions in online contexts for EFL students include time constraints, schools and teachers' unreadiness, and a large number of students. This study implies that with the beneficial advantages offered by differentiated learning in online learning, EFL teachers should observe the challenges and prepare necessary steps face the challenges from hindering the benefits of differentiated instructions for the students.